Measuring The Validity of Unilateral Non-Competition Clauses in Employment Agreements: A Civil and Employment Law Perspective - Rismarini, Kornelia; Rachmania, Bella Nadhillah; Arizal, Verly (Advances In Social Humanities Research, 2025)
This article examines the non-competition clause in employment agreements, particularly in the context of industrial inequality and the protection of workers' constitutional rights. Through a normative juridical approach and analysis of the Central Jakarta Court of International Relations (PHI) Decision No. 106/Pdt.Sus-PHI/2019/PN.Jkt.Pst. This article shows that non-competition clauses that are not proportionately arranged and without proper compensation can be declared null and void because they violate the principle of balance and the principle of the right to work. The ruling marks a paradigm shift in the court from a formalistic to a substantial approach in assessing employment contracts. The findings in this article also underscore the importance of regulatory reform and legal education for workers, in order to prevent exploitative clauses in employment agreements. This article recommends that treaty law in the context of employment should always be subject to the principles of substantive justice and protection of the weak.